Penapisan Varietas Padi Toleran Salinitas pada Lahan Rawa di Kabupaten Pesisir Selatan - M. Zulman Harja Utama; Widodo Haryoko; Rafli Munir; , Sunadi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The experiment was aimed to determine the most suitable method for selection of salt-tolerant, and to investigate the agronomic characteristics of salt-tolerant rice variety.  Two experiments were conducted to study the tolerance of 18 varieties to salt: 1) in situ screening of salt-tolerant varieties using completely randomized design, and 2) screening of salt-tolerant varieties using factorial experiment (varieties and salinity) with completely randomized design. The experiment showed that screening of rice variety that tolerant and sensitive to salt stress can be determined by comparing root dry weights in salt stressed condition and in unstressed condition, and in term of agronomical aspect, salt stress-tolerant rice showed good growth when planted in the saline field.   Key words: Screening, rice, swamp areas and salt stress